THE POTENTIAL OF PESANTREN IN SUSTAINABLE RURAL DEVELOPMENT - Fatimatuzzahroh, Feti; Abdoellah, Oekan S; Sunardi, Sunardi (SCAD Independent, 2015)
The number of pesantren that scattered in rural areas makes it as one of the potential of informal institutions in sustainable rural development. The aim of this study was to determine the potential of pesantren Buntet in sustainable rural development. The method used in this study was a qualitative method that carried out through unstructured interviews and observations that aim to describe the potential of the pesantren in supporting sustainable rural development. The results of the data analysis are interpreted using the theory of Pretty and Ward that used to analyze the potential of pesantren.Through this research was determined that Pesantren Buntet had a potential in terms of sustainable development activities which include social, economic, and environmental activity. Moreover, in term of institutional aspect Pesantren Buntet at the stage awareness interdependence. However, Pesantren Buntet not entirely on stage Awareness interdependence. Because in indicators of technological development, Pesantren Buntet is still at the stage 1 is reactive dependence, where the use of technology in these pesantren is still at the stage of eco-efficiency and harm reduction.